2009
DOI: 10.1002/ajmg.a.32900
|View full text |Cite
|
Sign up to set email alerts
|

High resolution genomic analysis of 18q− using oligo‐microarray comparative genomic hybridization (aCGH)

Abstract: The advent of oligonucleotide array comparative genomic hybridization (aCGH) has revolutionized diagnosis of chromosome abnormalities in the genetics clinic. This new technology also has valuable potential as a research tool to investigate larger genomic rearrangements that are typically diagnosed via routine karyotype. aCGH was used as a tool for the high resolution analysis of chromosome content in individuals with known deletions of chromosome 18. The aim of this study was to clarify the precise location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 19 publications
6
57
1
1
Order By: Relevance
“…Recurrent mutations have been observed in exon 18. The deletions are each unique and no clustering of breakpoints has been observed, which is in accordance with what is known of 18q deletions in general [Heard et al, 2009;Hasi et al, 2011].…”
Section: Mutation Spectrum and Genotype-phenotype Correlationsupporting
confidence: 88%
“…Recurrent mutations have been observed in exon 18. The deletions are each unique and no clustering of breakpoints has been observed, which is in accordance with what is known of 18q deletions in general [Heard et al, 2009;Hasi et al, 2011].…”
Section: Mutation Spectrum and Genotype-phenotype Correlationsupporting
confidence: 88%
“…These regions were never found to be hemizygous in the 260 individuals with molecularly characterized abnormalities. 2 Figure 1 shows a zoomed in view of band 18q21.2.…”
Section: Resultsmentioning
confidence: 99%
“…In our evaluation of more than 200 individuals with hemizygosity of Chromosome 18q, only two unrelated individuals have identical genomic aberrations. 1,2 In 2002, we reported that 72% of individuals with 18p deletions have breaks at the centromere. 3 However, array comparative genomic hybridization (aCGH) has revealed that even those with so-called "centromeric breaks" have breakpoints that fall into four groups with different genetic content (unpublished data).…”
mentioning
confidence: 99%
“…About 1/40,000 babies are born with a deletion in chromosome 18q (Unique, The Rare Chromosome Disorder Support Group, http:// www.rarechromo.org). A group of over 290 individuals with a terminal or interstitial deletion of 18q was analyzed using aCGH, and no overlaps of the deleted regions were found [Heard et al, 2009]. More than half of 16 individuals of the previous group with terminal deletion of 18q, with a breakpoint upstream CDH7 , have delayed myelination of the brain, foot anomalies, atretic and stenotic ear canals, hypospadias in males, tapered fingers, flat midface, proximally placed thumbs, and congenital heart anomalies [Cody et al, 2014].…”
Section: Discussionmentioning
confidence: 99%